Performance measurement design using objective matrix (Case study: an egg-laying chicken farming) - Afifah, Belia; Habibie, Indra; Zulfikar, Zulfikar; Nurkholis, Nurkholis; Am, Andri Nofiar; Putri, Dini Amalia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Increased demand and quality pressures are affecting businesses, as experienced by an Egg Laying Chicken Farming, a small and medium-sized enterprise (SME) Poultry Farm located in Salo Subdistrict, Kampar Regency, Riau Province. Previously, performance evaluations were solely based on monthly egg product sales. Therefore, this research aims to analyze the potential and constraints, and to prioritize strategies for business owners by comprehensively measuring business performance, thus allowing for the provision of suitable strategic recommendations. The measurement model is based on several indicators such as Productivity of Laying Hens, Effective Working Hours, Ratio of defect product, Equipment Productivity, and Productivity of Labor Involved, using the Objective Matrix (OMAX) method. The measurement results are analyzed using the Traffic Light System (TLS) to identify the ratio of indicators that fall below the standards set by the business owner, allowing for further analysis to obtain useful strategic recommendations for future productivity improvement.